Banana disease-suppressive soil drives Bacillus assembled to defense Fusarium wilt of banana - Fan, Huacai; He, Ping; Xu, Shengtao; Li, Shu; Wang, Yongfen; Zhang, Wenlong; Li, Xundong; Shang, Hui; Zeng, Li; Zheng, Si-Jun (Frontiers in Microbiology, 2023)
Fusarium wilt of banana (FWB) caused by Fusarium oxysporum f. sp. cubense tropical race 4 (Foc TR4), triggers a serious problem for sustainable banana production. Biological control is one of the effective measures to control this destructive disease. High-throughput sequencing of soil microorganisms could significantly improve the efficiency and accuracy of biocontrol strains screening. In this study, the soil microbial diversity of six main banana producing areas in Yunnan was sequenced by Illumina Miseq platform. The outcome of this study showed the genus of Chujaibacter, Bacillus and Sphingomonas were significantly enriched in microorganism community composition. Further correlation analysis with soil pathogen (Foc TR4) content showed that Bacillus was significantly negatively correlated with pathogen content. Therefore, we isolated and identified Bacillus from the disease-suppressive soils, and obtained a B. velezensis strain YN1910. In vitro and pot experiments showed that YN1910 had significant control effect (78.43%-81.76%) on banana Fusarium wilt and had significant growth promotion effect on banana plants.